Choice Determination Under Various Price Offer Frames - Deshpande, Rajesh (Indian Journal of Marketing, 2016)
Studies on prices have indicated varied learning of human behaviour in terms of how buyers perceive prices of products individually and how they think about prices when offered to them in a frame with some price offer combinations. Empirical studies have demonstrated that a buyer is likely to change his/her acceptance of a product due to not only the change in the price of the desired product, but also in part due to the change of prices of other products in a price frame. The buyer may even alter his/her preference in case the options to choose from increase or decrease in a given frame. A significant area of contribution to this subject has been done by Prospect Theory (PT), which highlights the impact of the reference point’s influence. The reference point enables a decision maker to evaluate the outcomes of his/her decision, that is, is the decision increasing my gains or reducing my losses ? Changes of frames, therefore, in substance alter a decision maker’s choice. This, as the PT concept suggests, is due to the fact that the position of a consumer to assess losses and gains alters within each frame.